2017
DOI: 10.1007/s00705-017-3422-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and pathogenic characterization of a pigeon paramyxovirus type 1 isolate reveals cross-species transmission and potential outbreak risks in the northwest region of China

Abstract: Pigeon paramyxovirus type-1 (PPMV-1) is enzootic in pigeons, causing severe economic loss in the poultry industry in many countries. However, the exact epidemic process of PPMV-1 transmission is still unclear. In this study, we analyzed the complete genome of the PPMV-1/SX-01/15 isolate. Sequence results show that the virus genome contains 15,192 nucleotides, with the gene order 3'-NP-P-M-F-HN-L-5'. Phylogenetic analysis revealed that this genome belongs to subgenotype VIc in class II. The mean death time (MDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…However, a recent study showed that the pathogenicity and transmission of virulent NDVs had no significant differences in young and adult chickens [45]. In our study, we found that age at infection had an impact on the outcome of PPMV-1 infection in pigeons, which was generally consistent with clinical cases in which the morbidity and mortality of younger pigeons were significantly higher than those of older pigeons [13,18]. These results indicated that the age of birds might affect PPMV-1, but not other NDV infections.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, a recent study showed that the pathogenicity and transmission of virulent NDVs had no significant differences in young and adult chickens [45]. In our study, we found that age at infection had an impact on the outcome of PPMV-1 infection in pigeons, which was generally consistent with clinical cases in which the morbidity and mortality of younger pigeons were significantly higher than those of older pigeons [13,18]. These results indicated that the age of birds might affect PPMV-1, but not other NDV infections.…”
Section: Discussionsupporting
confidence: 88%
“…At 3 and 7 days post-infection (DPI), we euthanized three inoculated pigeons and determined the virus titers in the brain and lungs. To detect virus shedding, oropharyngeal and cloacal swabs were collected at 3,5,7,9,11,13,17, and 21 DPI and suspended in 1000 µL PBS with antibiotics (penicillin and amphotericin B, 4000 U/mL; streptomycin, 2 mg/mL). All collected samples were stored at −80 • C until further use.…”
Section: Pathogenicity and Transmission In Pigeons Of Different Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with three class I sequences without a recorded host, the sequences collected from the latter four host groups were categorized into an ambiguous group (i.e., "other avian taxa" henceforth) given small sample sizes. The majority of class II viruses collected between 2006 and 2016 originated from Anseriformes (171), domestic chickens (569), Columbiformes (220), other Galliformes (34), Psittaciformes (11), and Suliformes (19) hosts. Similar to class I, 43 class II sequences from rare or unrecorded host groups were collected into the other avian taxa category.…”
Section: Host and Geographic Characteristicsmentioning
confidence: 99%
“…This suggests that though the initial transmission of wild bird virus into a domestic population may not have significant epidemiological consequences, the repeated transference of virulent viruses between domestic and wild birds likely affects global APMV-1 dynamics. Even though other investigations have found evidence for APMV-1 migration between hosts and geographic regions [9,12,[16][17][18][19], a globally-distributed analysis of APMV-1 viral migration has not yet been performed. Presence of virulent APMV-1 in poultry is reportable to the World Organisation for Animal Health (OIE) and may result in trade restrictions [20]; therefore, understanding the patterns of viral migration between world regions and host types would be useful for efforts directed towards preventing and limiting the spread of ND among wild and domestic birds.…”
Section: Introductionmentioning
confidence: 99%